AKTIVITAS BELAJAR SISWA KELAS X BUSANA PADA MATA PELAJARAN BUSANA WANITA DI SMK NEGERI 6 PADANG - Kusuma, Nella; Ramainas, Ramainas; Adriani, Adriani (Journal of Home Economics and Tourism, 2013)
This research to describe study activity students of X degree of fashion to regard women fashion subject such as: visual activity, oral activity, listening activity, and metric activity. The kind of this research is quantitative descriptive. The population is all students of X degree of fashion SMK N 6 Padang which are 26 students. All population is the sample. Data analysis did by determining presentation, chategorize and respondents total achievement. The result shows that: (1) visual activity show that high category (78,6%). (2) Oral activity show that high category (77,87%). (3) Listening activity show that high category (70%). (4) Metric activity show that high category (77,69%). Keywords: Study activity, Subject, women Fashion